MODEL KEPUTUSAN PEMBELIAN MELALUI IMPLEMENTASI STRATEGI BAURAN PROMOSI PADA BISNIS ONLINE (STUDI KASUS: PADA TRANSPORTASI PT GOJEK INDONESIA) - Soegoto, Eddy Soeryanto (Majalah Ilmiah UNIKOM, 2018)
The goals of the research are to divulge the implementation of promotion mix strategy and its impact on the purchase decision towards the Go-jek online transportation service. The research-er uses a quantitative approach, descriptive and verified design, and survey method. As much as 100 respondents have been drawn using the purposive approach from the population of the Go-jek consumers. The data collection employs questionnaire and the path analysis procedure has been used as the data analysis technique. The findings of this research are as follows: the varia-bles of advertising, sales promotion, personal sale, publicity and community relationship fall into moderate – good category; moreover both partially and simultaneously the variables of advertis-ing, sales promotion, personal sale, publicity and community relationship, as well as direct mar-keting affect the purchase decision.